The Association Between Serum Vitamin D Status and Cardiometabolic Risk Factors in Extremely Obese Adults: A Cross-Sectional Study - Yan Zhou; Chunyan Wang; Zhixing Wang; Xiaojing Wang (International Journal of Endocrinology)
Conclusions: Vitamin D deficiency is highly prevalent in extremely obese individuals in China, exhibiting significant correlations with higher BMI and lower HDL-c/ApoA1. Our findings underscore the importance of vitamin D deficiency as a correlate of cardiovascular risk. Prospective studies and randomized clinical trials are warranted to determine the effect of 25(OH) D on other cardiometabolic parameters.